Factors associated with domestic violence in women: systematic ecological review - Brito Jiménez, Ivone Tatiana; Rodríguez Ávila, Nuria (Revista Cuidarte, 2024)
Highlights• The ecological model analyzes potential factors related to domestic violence against women, considering interactions within the physical and social environment.• Individual, family, community, and sociocultural factors contribute to a better understanding of the complexity of domestic violence.• The elements that affect the onset and continuation of domestic violence provide a comprehensive perspective, which is essential for developing effective intervention strategies.• The systematic review examines a variety of factors contributing to domestic violence against women and provides a holistic view of the issue.Introduction: Domestic violence is a multi-causal situation that impacts women, exposing them to significant structural inequalities. Objective: To identify patterns that perpetuate domestic violence in women through a comprehensive review of the literature, using the ecological model to understand the underlying factors. Materials and Methods: A systematic literature review was conducted in Spanish, English, and Portuguese on patterns associated with domestic violence against women, using the PubMed, Scopus, Sociological Abstracts, and JSTOR databases, following the PRISMA method. Relevant studies were identified and selected based on predefined criteria, and their quality was assessed. Results:   Twenty-two studies were selected that met the relevance and quality criteria. The review reveals that domestic violence is perpetuated through various systems: in the microsystem, patterns such as low educational level, alcohol and drug consumption, and emotional dependence; in the mesosystem, lack of life skills, inability to make decisions, and child abuse; in the exosystem, low income, poverty, unemployment, and criminal records; and in the macrosystem, husband’s controlling behavior and society. Discussion: The comprehensive analysis from different microsystemic, mesosystemic, exosystemic, and macrosystemic perspectives reveals gaps in existing knowledge and reinforces hypotheses about the underlying mechanisms, corroborating similar problems in other studies.  Conclusion: The study provides a comprehensive understanding of domestic violence by analyzing patterns from different systems. This approach guides the development of more effective and informed prevention interventions and policies.How to cite this article: Brito Jiménez Ivone Tatiana, Rodríguez Ávila Nuria. Factors associated with domestic violence in women: systematic ecological review. Revista Cuidarte. 2025;16(1):e3857.   https://doi.org/10.15649/cuidarte.3857
Keywords: Domestic Violence; Women; Social Determinants of Health; Systematic Review